Evaluasi Kecernaan Pakan Vegetarian pada Lobster Air Tawar Marron (Cherax cainii) Menggunakan Kromium Oksida sebagai Marker (VEGETARIAN FEED DIGESTION EVALUATION ON MARRON FRESHWATER LOBSTER (CHERAX CAINII) USING CHROMIUM OXIDE AS A MARKER) - Saputra, Ishaaq; Indaryanto, Forcep Rio (Jurnal Veteriner, 2019)
The range of protein requirements in Forty marron (Cherax cainii) makes it possible to use artificial feed based on non-fish meal or from plant material. The aim of this study was to evaluate vegetarian feed digestibility on marron freshwater lobster (Cherax cainii) using chromium oxide as a marker. The study was conducted at the Curtin Aquatic Research Laboratory, Curtin University, Perth, Western Australia. A 40 freshwater lobsters with an initial weight of 60.07 ± 5.33 g were kept in 10 aquariums. Observations carried out for 10 days. Results indicated that total digestibility and survival rate of marron given commercial feed with protein sources of soybean meal were not significantly different from commercial feed with fish meal protein sources (P <0.05). However, relative growth, FCR and FER forty marron given commercial feed with fish meal protein sources is better.